Electrode for producing ammonia by electro-catalysis of nitrate based on layered structure material
A composite electrode material with intercalated polyoxometalates in layered double hydroxides enhances nitrate reduction efficiency and selectivity, addressing stability and selectivity issues in existing technologies.
Patent Information
- Application Number
- CN202411279021.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-27
AI Technical Summary
Existing electrocatalytic materials for nitrate reduction to ammonia face challenges in selectivity and stability due to excessive ion adsorption, ion migration rate limitations, and structural defects, leading to low Faraday efficiency and high production of by-products.
A composite electrode material is developed using a layered structure material combined with polyoxometalates (POMs) intercalated into layered double hydroxides (LDHs), optimizing the d-band center and electron transfer pathways to enhance nitrate reduction efficiency and selectivity.
The composite material significantly improves the efficiency and selectivity of nitrate reduction to ammonia, achieving high Faraday efficiency and stability under normal conditions, suitable for large-scale industrial applications.
Smart Images

Figure CN119194497A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical catalysis, and particularly relates to an electrocatalytic electrode for electrochemically reducing nitrate to produce ammonia, and a preparation method and application thereof. Background Art
[0002] Ammonia (NH3) is a key raw material for nitrogen fertilizer production, with an annual global production of about 180 million tons, mainly relying on the energy-intensive Haber-Bosch process. This process accounts for 1.5% of global energy consumption and emits about 150 million tons of CO2 per year. Nitrogen (N2) reacts with hydrogen (H2) to produce ammonia under high temperature (400-500°C) and high pressure (15-25MPa). Due to high energy consumption and high emissions, this process faces sustainability challenges.
[0003] Electrochemical nitrogen reduction technology is a potential alternative method that reduces N2 by simulating the microbial nitrogen fixation process at room temperature and pressure. However, due to the high dissociation energy of the N≡N bond of 941 kJ / mol and the low solubility of nitrogen in water, the yield of electrochemical ammonia synthesis is 2 to 3 orders of magnitude lower than that of the Haber-Bosch process.
[0004] In contrast, electrochemical reduction of nitrate to produce ammonia is due to the nitrate ion (NO3 - ) has become a research hotspot due to its low N=O bond dissociation energy (204kJ / mol). NO3 not only has an advantage in reaction kinetics, but is also widely present in agricultural runoff and industrial wastewater, making it an ideal raw material for sustainable ammonia synthesis. - Synthetic ammonia is expected to reduce energy consumption and environmental pollution.
[0005] In the process of electrochemical reduction of nitrates to produce ammonia, the choice of electrode materials plays a crucial role in reaction efficiency and product selectivity. Although traditional electrocatalytic materials such as precious metals (such as Pt, Pd) and their oxides (such as RuO2, IrO2) have high catalytic activity, their high cost and limited resource reserves limit their promotion in large-scale industrial applications. In contrast, non-precious metal materials (such as Cu, Fe-based catalysts) are lower in cost, but still have significant deficiencies in selectivity and stability, and generate more by-products such as N2 and NO, resulting in the Faraday efficiency (FE) of ammonia being generally less than 50%.
[0006] In order to improve the efficiency of nitrate reduction to ammonia, the development of new electrocatalytic materials has become a research focus. Designs based on layered structural materials have gradually attracted attention. These materials include but are not limited to layered double hydroxides (LDHs), graphite carbon nitride (g-C3N4) and layered disulfides (such as MoS2). These materials have certain advantages in catalytic reactions due to their adjustable interlayer spacing, high specific surface area and good anion exchange capacity. Patent CN 118223061 discloses a method of using foam copper to support cobalt-iron layered double hydroxide as a catalytic electrode material, while patent CN 113926456 introduces a preparation method and application of a NiFe-LDH catalyst based on nano-iron support. LDHs have certain advantages in catalytic reactions due to their adjustable interlayer spacing, high specific surface area and good anion exchange capacity. However, layered structural materials still face some challenges in application. Excessive ion adsorption may shield some active sites, while the limitation of ion migration rate and structural defects may further reduce their selectivity and stability. Summary of the invention
[0007] Based on the above-mentioned prior art problems, the present invention intends to provide a composite electrode material based on a layered structure material for electrocatalytic nitrate production of ammonia, so as to solve the problem that the layered structure material in the electrocatalytic material of the ammonia production electrode reduces the electrode selectivity and stability due to excessive ion adsorption shielding of some active sites, ion migration rate limitation and structural defects. By using a composite material based on a layered structure material as an electrocatalytic material in the ammonia production electrode, the reaction efficiency and selectivity of electrochemical nitrate reduction to ammonia production are improved.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme.
[0009] First, the present invention provides an electrode for electrocatalytic reduction of nitrate to produce ammonia based on layered structural materials, the electrode comprising a base nickel foam, and an electrocatalytic material uniformly deposited on the surface of the nickel foam, the electrocatalytic material being a composite material based on layered structural materials; the composite material is a composite of a layered structural material and an intercalation material polyoxometalates (POMs), and the layered structural material and POMs are compositely constructed into a composite structure having an intercalation structure, specifically: POMs are functional intercalation substances, inserted between layers of the layered structural material to form an intercalation structure. More specifically, the layered structural material is a layered double hydroxide (CuNi-LDH) composed of copper and nickel elements or other materials with a layered structure such as graphite phase carbon nitride (g-C3N4) and layered disulfide (such as MoS2). More specifically, the polyoxometalates (POMs) include VO3 - 、MoO2 - 、NbO3 - WO4 2- One or more polyoxometalates.
[0010] The ammonia-producing electrode uses the composite material as an electrocatalytic material. The POM molecules in the composite material can be embedded between the layers of the layered material to form a POM intercalation layer, and the NO3 - Adsorption energy of NO3 - The reduction pathway of nitrate reduction can be optimized to enhance the electrocatalytic activity and selectivity and improve the efficiency of nitrate reduction to produce ammonia.
[0011] In various embodiments of the present invention, in the first preferred embodiment, in the electrocatalytic material, the layered structural material is a layered double hydroxide (CuNi-LDH) composed of copper and nickel elements, and its components are Cu(OH)2 and Ni(OH)2; the POM intercalation material is VO3 polyoxometalate. More specifically, in the electrocatalytic material, the molar percentage of copper and nickel elements in CuNi-LDH is 40-60%:40-60%, and the proportion of the POM intercalation material is 2-3% of the total molar amount of Cu(OH)2 and Ni(OH)2 in the layered double hydroxide in the electrocatalytic material.
[0012] In the electrocatalytic material of the second preferred embodiment, the layered structure material is a layered double hydroxide (CuNi-LDH) composed of copper and nickel elements, and its components are Cu(OH)2 and Ni(OH)2; the POM intercalation material is MoO2 polyoxometalate. More specifically, in the electrocatalytic material, the molar percentage of copper and nickel elements in CuNi-LDH is 40-60%:40-60%; the proportion of the POM intercalation material is 2-3% of the total molar amount of Cu(OH)2 and Ni(OH)2 in the layered double hydroxide in the electrocatalytic material.
[0013] In the electrocatalytic material of the third preferred embodiment: the layered structure material is still CuNi-LDH, and NbO3 is intercalated - Polyoxometalates. The molar percentage of copper and nickel in CuNi-LDH is 40-60%:40-60%, and the proportion of POM intercalation material is 2-3% of the total molar amount of Cu(OH)2 and Ni(OH)2 in the layered double hydroxide in the electrocatalytic material.
[0014] In the electrocatalytic material of the fourth preferred embodiment: WO4 is intercalated in CuNi-LDH 2- Polyoxometalate: The molar percentage of copper and nickel is 40-60%, and the proportion of POM intercalation material is 2-3% of the total molar amount of Cu(OH)2 and Ni(OH)2 in the layered double hydroxide in the electrocatalytic material.
[0015] The present invention forms an electrode for electrocatalytic reduction of nitrate to produce ammonia by electro-depositing a composite material of a POM intercalated layered structure material on the surface of nickel foam. The inventor mainly bases on the following reasons.
[0016] The first invention analyzes the process of electrocatalytic nitrate production of ammonia, the nitrate reduction reaction (NO3 - The core of RR) lies in multi-electron transfer and efficient NO3 - Adsorption and reduction. NO3 - The reduction to NH3 involves a complex multi-step reaction, mainly including: 1) NO3 - Adsorbed on the catalyst surface; 2) through multiple electron transfer steps, NO3 - Gradually reduced to intermediates (such as NO2 - , NO, NH2OH, etc.); 3) finally reduced to NH3. In this process, the d-band center position of the catalyst is very important, and its main influence is NO3 - adsorption energy and electron transfer efficiency. Different from hydrolysis reactions such as OER, NO3 - RR emphasizes whether the surface of the material can effectively adsorb NO3 -And provide an appropriate electron transfer pathway, which is an important factor affecting the efficiency of electrocatalytic nitrate production of ammonia.
[0017] Therefore, the inventors formed a composite material by constructing a POM intercalation interlayer structure material LDH, which can be used in NO3 - The main advantages reflected in RR include the following aspects:
[0018] 1) d-band center regulation: POM intercalation adjusts the electronic structure of LDH materials, making the d-band center closer to the Fermi level and increasing NO3 - By enhancing the adsorption energy of NO3 - Due to the interaction with the catalyst surface, the composite material of POM intercalated LDH can more efficiently adsorb and reduce NO3 - , which is crucial to achieve efficient multi-electron transfer.
[0019] 2) Optimization of multi-electron transfer pathways: NO3 - RR requires the transfer of multiple electrons, and the introduction of POM not only provides multiple electron donors, but also effectively reduces the energy barrier of the reaction. The multi-center active sites of POM enable electrons to be transferred from the catalyst to NO3 more efficiently. - , thereby promoting NO3 - Conversion to NH3.
[0020] 3) Inhibit side reactions: in NO3 - In RR, avoiding side reactions (such as hydrogen evolution reaction) is the key to ensuring high selectivity of ammonia. Another significant effect of POM intercalation is to optimize the charge distribution between LDH layers, reduce the possibility of hydrogen evolution reaction, and thus improve NO3 - Faradaic efficiency and ammonia selectivity of RR.
[0021] The present invention realizes the optimal performance of the composite material in the electrocatalytic process by reasonably designing the type and intercalation ratio of POM.
[0022] Another object of the present invention is to provide a method for preparing the above-mentioned electrode for electrocatalytic reduction of nitrate to produce ammonia, which comprises the following steps.
[0023] (1) Remove impurities from the surface of nickel foam, wash and dry it for later use.
[0024] (2) adding a non-precious metal salt forming a layered structure material according to molar percentage, dissolving it in deionized water, preferably adding Cu(NO3)2·3H2O and Ni(NO3)2·6H2O in a molar ratio of 40-60%:40-60% to form a CiNi-LDH layered structure material; then adding a POM precursor (such as Na2WO4·2H2O, NaVO3, NaMoO2·2H2O or NaNbO3) forming a POM intercalation material; adjusting the pH value of the solution to an appropriate range, and ultrasonically treating to ensure uniform mixing of the solution, to obtain a precursor solution A. The amount of the POM precursor added to form the intercalation material is added in a ratio of 2-3% of the total molar ratio of the intercalation material to the non-precious metal salt forming the layered structure material.
[0025] (3) The precursor solution A prepared in step 2 and the pretreated nickel foam substrate are placed in a hydrothermal reaction kettle, and the reaction kettle is placed at 100-130° C. for a hydrothermal reaction for 6-12 hours.
[0026] (4) After the hydrothermal reaction is completed, the nickel foam electrode is taken out, washed and dried; and an ammonia-producing electrode having a POM intercalation layer and a composite material based on a layered structure material as an electrocatalytic material is obtained.
[0027] As a preferred embodiment of the present invention, in step 1), the process of removing impurities on the surface of the nickel foam includes sequentially immersing the nickel foam in a 1-3M acidic solution (such as hydrochloric acid, nitric acid, sulfuric acid or other suitable inorganic acid) for 5-30 minutes of ultrasonic treatment, and then performing ultrasonic cleaning in deionized water for 5-30 minutes to remove acid residues. Afterwards, the nickel foam is placed in an organic solvent (such as anhydrous ethanol, acetone, methanol or other suitable organic solvent) for 5-30 minutes of ultrasonic treatment to further clean the surface of the nickel foam.
[0028] As a preferred embodiment of the present invention, in step 2), the non-precious metal in the non-precious metal salt forming the layered structure material can be any non-precious metal, including but not limited to copper (Cu), nickel (Ni), iron (Fe), zinc (Zn), cobalt (Co), magnesium (Mg), aluminum (Al), etc. Non-precious metals that can form stable layered double hydroxides or other layered structures are applicable. In step 2), the POM precursor forming the POM intercalation material can be any polyoxometalate POM that can form an intercalation structure, including but not limited to tungstate (WO4 2- ), vanadate (VO3 - ), molybdate (MoO2 - ), niobate (NbO3 - ), phosphotungstic acid (H3PW 12 O 40 - ), phosphomolybdic acid (H3PMo12 O 40 - ), silicotungstic acid (H4SiW 12 O 40 - ) and other polyoxometalates that can form stable intercalation composite materials with layered structure materials.
[0029] As a preferred embodiment of the present invention, during the hydrothermal reaction in step 3), the ratio of the volume of the solution in the hydrothermal reaction kettle to the surface area of the nickel foam electrode can be 5 to 20 mL / cm 2 , preferably 8 to 15 mL / cm 2 Within this range, the ratio of solution to electrode area can be adjusted according to specific experimental conditions to ensure the optimal formation and performance of the POM intercalated layered structure material composite.
[0030] As a preferred embodiment of the present invention, in step 2), the pH value of the solution is adjusted by adding regulators such as urea and ammonium fluoride (NH4F) to the solution. Specifically, the amount of urea added is 0.4-0.6M, and the amount of ammonium fluoride added is 0.2-0.4M. By adding these regulators, the pH value of the solution can be maintained in the range of 8-10. This can ensure the optimal formation of the POM intercalated layered structure material composite during the hydrothermal reaction, and effectively inhibit possible side reactions, thereby improving the electrochemical performance of the composite material.
[0031] A method for producing ammonia by reducing nitrates, the present invention uses the above-mentioned electrocatalytic reduction nitrate ammonia production electrode as a high-efficiency self-supporting integrated electrode, which is applied to an electrochemical system to electrocatalytically reduce nitrates to produce ammonia. The method realizes efficient reduction of nitrates under normal temperature and pressure conditions by driving an external electric field, achieving a highly selective ammonia production effect.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention prepares a layered structure material with polyoxometalate (POM) intercalation on the surface of nickel foam by a hydrothermal method, forming a stable layered nanostructure. This structural design significantly increases the active surface area and the number of reaction sites of the electrode, thereby improving the efficiency and activity of the nitrate reduction reaction.
[0034] 2. Through the synergistic effect of POM intercalation and layered structural materials, the adsorption capacity of NO3- is effectively enhanced, and the occurrence of side reactions (such as hydrogen evolution reaction) is inhibited by the intercalation structure. By optimizing the type and intercalation ratio of POM, high ammonia production Faraday efficiency and high ammonia selectivity are achieved.
[0035] 3. The electrode material of the present invention exhibits excellent electrochemical stability at room temperature and pressure. After multiple cycles of reaction, the conversion rate of nitrate remains at a high level, which is suitable for long-term operation of NO3 - Restore process.
[0036] 4. The electrocatalytic process of the present invention exhibits good performance in a wide potential range, can effectively carry out nitrate reduction reaction under different potential conditions, while maintaining a high ammonia production efficiency, and is suitable for practical applications under various operating conditions.
[0037] 5. The preparation method of the present invention is simple and efficient, does not involve complicated processes, and the materials used are all non-precious metals, which are low in cost and have broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 In order to use the electrode prepared in Example 1 of the present invention in a specific electrolyte environment (50 mg / L NO3 - -N, 0.1mol / L SO4 2- ) under different voltage conditions after 7200s of nitrate reduction to ammonia reaction.
[0039] Figure 2 In order to use the electrode prepared in Example 2 of the present invention in a specific electrolyte environment (50 mg / L NO3 - -N, 0.1mol / L SO4 2- ) under different voltage conditions after 7200s of nitrate reduction to ammonia reaction.
[0040] Figure 3 In order to use the electrode prepared in Example 3 of the present invention in a specific electrolyte environment (50 mg / L NO3 - -N, 0.1mol / L SO4 2- ) under different voltage conditions after 7200s of nitrate reduction to ammonia reaction.
[0041] Figure 4 In order to use the electrode prepared in Example 4 of the present invention in a specific electrolyte environment (50 mg / L NO3 - -N, 0.1mol / L SO4 2- ) under different voltage conditions after 7200s of nitrate reduction to ammonia reaction.
[0042] Figure 5 In order to use the electrode prepared in Comparative Example 1 of the present invention in a specific electrolyte environment (50 mg / L NO3 - -N, 0.1mol / L SO4 2-) under different voltage conditions after 7200s of nitrate reduction to ammonia reaction.
[0043] Figure 6 In order to use the electrode prepared in Comparative Example 2 of the present invention in a specific electrolyte environment (50 mg / L NO3 - -N, 0.1mol / L SO4 2- ) under different voltage conditions after 7200s of nitrate reduction to ammonia reaction.
[0044] Figure 7 This is a Faradaic efficiency (FE) diagram of Application Examples 1 to 4 after 6 hours of continuous reaction. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with specific embodiments. The embodiments are provided to help those skilled in the art to better understand and apply the present invention, but should not be regarded as any limitation to the scope of protection of the present invention. It should be pointed out that for those of ordinary skill in the art, various modifications, improvements or equivalent substitutions made without departing from the concept of the present invention should be regarded as belonging to the scope of protection of the present invention.
[0046] Example 1
[0047] A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia comprises the following steps:
[0048] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0049] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 50%:50%, dissolved in deionized water, and NaVO3 was added (the intercalation ratio was 2% by molar ratio, that is, the amount of NaVO3 added was: the molar ratio of the sum of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O was 2%). In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 8-9. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0050] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 8 mL / cm 2 The reactor was placed at 120°C for 6 hours. During this process, VO3 - Intercalate into the LDH interlayer to form a stable composite material.
[0051] (4) Post-treatment: After the hydrothermal reaction, the nickel foam electrode was taken out and rinsed three times with deionized water to remove the surface residues. It was then dried in a vacuum drying oven at 80 °C for 12 h and cooled to room temperature to obtain the final loaded LDH / VO3 - Electrode material of the electrode.
[0052] Example 2
[0053] A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia comprises the following steps:
[0054] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0055] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 50%:50%, dissolved in deionized water, and Na2WO4·2H2O was added (the intercalation ratio was 2%, that is, the amount of Na2WO4·2H2O added was: the molar ratio of the sum of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O was 2%). In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 8-9. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0056] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 8 mL / cm 2 The reactor was placed at 120°C for 6 hours. During this process, WO4 2- Intercalate into the LDH interlayer to form a stable composite material.
[0057] (4) Post-treatment: After the hydrothermal reaction, the nickel foam electrode was taken out and rinsed three times with deionized water to remove the surface residue, and then dried in a vacuum drying oven at 80°C for 12 hours. After cooling to room temperature, the final loaded LDH / WO4 was obtained. 2- Electrode material of the electrode.
[0058] Example 3
[0059] A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia comprises the following steps:
[0060] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0061] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 50%:50%, dissolved in deionized water, and Na2MoO4·2H2O was added (the intercalation ratio was 2%, that is, the amount of Na2MoO4·2H2O added was: the molar ratio of the sum of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O was 2%). In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 8-9. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0062] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 8 mL / cm 2 The reactor was placed at 120°C for 6 hours. During this process, MoO4 2- Intercalate into the LDH interlayer to form a stable composite material.
[0063] (4) Post-treatment: After the hydrothermal reaction, the nickel foam electrode was taken out and rinsed three times with deionized water to remove the surface residues, and then dried in a vacuum drying oven at 80°C for 12 hours. After cooling to room temperature, the final loaded LDH / MoO4 was obtained. 2- Electrode material of the electrode.
[0064] Example 4
[0065] A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia comprises the following steps:
[0066] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0067] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 50%:50%, dissolved in deionized water, and NaNbO3 was added (the intercalation ratio was 2%, that is, the amount of NaNbO3 added was: the molar ratio of the sum of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O was 2%). In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 8-9. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0068] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 8 mL / cm 2 The reactor was placed at 120°C for 6 hours. During this process, NbO3 - Intercalate into the LDH interlayer to form a stable composite material.
[0069] (4) Post-treatment: After the hydrothermal reaction, the nickel foam electrode was taken out and rinsed three times with deionized water to remove the surface residues, and then dried in a vacuum drying oven at 80°C for 12 hours. After cooling to room temperature, the final loaded LDH / NbO3 was obtained. - Electrode material of the electrode.
[0070] Example 5
[0071] A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia comprises the following steps:
[0072] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0073] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 40%:60%, dissolved in deionized water, and NaVO3 was added (the intercalation ratio was 3%, that is, the amount of NaVO3 added was: the molar ratio of the sum of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O was 3%). In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 9-10. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0074] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 5 mL / cm 2 The reactor was placed at 100°C for 12 hours. During this process, VO3 - Intercalate into the LDH interlayer to form a stable composite material.
[0075] (4) Post-treatment: After the hydrothermal reaction, the nickel foam electrode was taken out and rinsed three times with deionized water to remove the surface residues. It was then dried in a vacuum drying oven at 80 °C for 12 h and cooled to room temperature to obtain the final loaded LDH / VO3 - Electrode material of the electrode.
[0076] Example 6
[0077] A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia comprises the following steps:
[0078] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0079] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 60%:40%, dissolved in deionized water, and NaVO3 was added (the intercalation ratio was 2.5%, that is, the amount of NaVO3 added was: the molar ratio of the sum of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O was 2.5%). In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 8-9. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0080] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 15 mL / cm 2 The reactor was placed at 130°C for 6 hours. During this process, VO3 - Intercalate into the LDH interlayer to form a stable composite material.
[0081] (4) Post-treatment: After the hydrothermal reaction, the nickel foam electrode was taken out and rinsed three times with deionized water to remove the surface residues. It was then dried in a vacuum drying oven at 80 °C for 12 h and cooled to room temperature to obtain the final loaded LDH / VO3 - Electrode material of the electrode.
[0082] The embodiments listed above are only a few of the many examples explored by the inventors in the present invention. In the process of exploring the key parameters, the process parameters in the above embodiments are adjusted within a certain range, which can also achieve the purpose of the invention and achieve the equivalent effects of the following application examples 1 to 4. For example: the molar ratio of the raw materials Cu(NO3)2·3H2O and Ni(NO3)2·6H2O for forming the layered structure material CuNi-LDH is in the range of 40-60%:40-60%, the molar ratio of each POM intercalation material to the layered structure material is 2%-3%, the pH of solution A in step 2) is adjusted to 8-10, and during the hydrothermal reaction in step 3), the ratio of the solution volume to the area of the nickel foam electrode is maintained at 5-20mL / cm 2 , an ammonia producing electrode that can achieve the purpose of the present invention can be obtained.
[0083] Application Example 1
[0084] Electrocatalytic reduction of nitrate to produce ammonia, the steps are as follows:
[0085] The electrode prepared in Example 1 was clamped in the working electrode clamp and placed together with the reference electrode saturated silver chloride electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 --N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell with electrolyte.
[0086] Then, multiple linear sweep voltammetric curve tests are performed in the potential range of -1.2 to -1.8 V vs. Ag / AgCl until the curves of two adjacent tests are exactly the same.
[0087] The electrolyte was replaced and it tests were carried out at four potentials of -1.2, -1.4, -1.6 and -1.8 V respectively. The test time was 7200 s. Samples were taken every 1200 s and kept for later use. Each set of experiments was repeated at least three times.
[0088] In addition, using NaNO3 and NaNO2 as standard samples, high performance ion chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0089] like Figure 1 The test results show that at room temperature and pressure, LDH / VO3 - The electrode tested at a voltage of -1.2 V had the best effect. The analysis showed that the conversion rate of nitrate was 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 100%. When the reaction lasted for 3600 seconds, the conversion rate of nitrate had reached 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 100%.
[0090] Application Example 2
[0091] Electrocatalytic reduction of nitrate to produce ammonia, the steps are as follows:
[0092] The electrode prepared in Example 2 was clamped in the working electrode clamp and placed together with the reference electrode saturated silver chloride electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 - -N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell with electrolyte.
[0093] Then, multiple linear sweep voltammetric curve tests are performed in the potential range of -1.2 to -1.8 V vs. Ag / AgCl until the curves of two adjacent tests are exactly the same.
[0094] The electrolyte was replaced and it tests were carried out at four potentials of -1.2, -1.4, -1.6 and -1.8 V respectively. The test time was 7200 s. Samples were taken every 1200 s and kept for later use. Each set of experiments was repeated at least three times.
[0095] In addition, using NaNO3 and NaNO2 as standard samples, high performance ion chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0096] like Figure 2 The test results show that at room temperature and pressure, LDH / WO4 2- The electrode tested at a voltage of -1.8 V had the best effect. The analysis showed that the conversion rate of nitrate was 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 100%. When the reaction lasted for 4800 seconds, the conversion rate of nitrate had reached 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 100%.
[0097] Application Example 3
[0098] Electrocatalytic reduction of nitrate to produce ammonia, the steps are as follows:
[0099] The electrode prepared in Example 3 was clamped in the working electrode clamp and placed together with the reference electrode saturated silver chloride electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 - -N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell with electrolyte.
[0100] Then, multiple linear sweep voltammetric curve tests are performed in the potential range of -1.2 to -1.8 V vs. Ag / AgCl until the curves of two adjacent tests are exactly the same.
[0101] The electrolyte was replaced and it tests were carried out at four potentials of -1.2, -1.4, -1.6 and -1.8 V respectively. The test time was 7200 s. Samples were taken every 1200 s and kept for later use. Each set of experiments was repeated at least three times.
[0102] In addition, using NaNO3 and NaNO2 as standard samples, high performance ion chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0103] like Figure 3 The test results show that at room temperature and pressure, LDH / MoO4 2- The electrode tested at a voltage of -1.6 V had the best effect. The analysis showed that the conversion rate of nitrate was 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 100%. When the reaction lasted for 3600 seconds, the conversion rate of nitrate had reached 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 100%.
[0104] Application Example 4
[0105] Electrocatalytic reduction of nitrate to produce ammonia, the steps are as follows:
[0106] The electrode prepared in Example 4 was clamped in the working electrode clamp and placed together with the reference electrode saturated silver chloride electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 - -N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell with electrolyte.
[0107] Then, multiple linear sweep voltammetric curve tests are performed in the potential range of -1.2 to -1.8 V vs. Ag / AgCl until the curves of two adjacent tests are exactly the same.
[0108] The electrolyte was replaced and it tests were carried out at four potentials of -1.2, -1.4, -1.6 and -1.8 V respectively. The test time was 7200 s. Samples were taken every 1200 s and kept for later use. Each set of experiments was repeated at least three times.
[0109] In addition, using NaNO3 and NaNO2 as standard samples, high performance ion chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0110] like Figure 4 The test results show that at room temperature and pressure, LDH / / NbO3 - The electrode had the best test effect at a voltage of -1.8 V. The analysis showed that the conversion rate of nitrate was 100%, the generation rate of nitrite was 0%, and the generation rate of ammonia was 97.94%.
[0111] Application Example 5
[0112] Electrocatalytic reduction of nitrate to produce ammonia, the steps are as follows:
[0113] The electrodes prepared in Examples 1 to 4 were clamped in the working electrode clamp and placed together with the saturated silver chloride electrode reference electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 - -N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell, the electrolyte in the electrolytic cell is renewed every 120 minutes.
[0114] The IT test was performed at a potential of -1.4 V and a single test lasted for 6 hours to evaluate the stability.
[0115] In addition, using NaNO3 as a standard sample, liquid chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0116] At room temperature and pressure, the LDH / POM composite electrodes prepared in Examples 1 to 4 all exhibited excellent catalytic activity and stability in the electrocatalytic nitrate reduction reaction at a potential of -1.4 V. After 6 hours of IT testing, the Faraday efficiency (FE) of the four electrodes remained above 80%. The test results are as follows Figure 7 As shown, these materials have high stability in the process of nitrate reduction to produce ammonia and show good application prospects.
[0117] Comparative Example 1
[0118] A method for preparing an electrode for producing ammonia by electrocatalytic reduction of nitrate by LDH comprises the following steps:
[0119] (1) Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes each to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature for use.
[0120] (2) Preparation of hydrothermal reaction precursor solution: Cu(NO3)2·3H2O and Ni(NO3)2·6H2O were weighed at a molar percentage of 50%:50% and dissolved in deionized water. In order to adjust the pH value of the solution, urea (0.4-0.6M) and ammonium fluoride (0.2-0.4M) were added to the solution to maintain the pH value of the solution in the range of 8-9. Then, after ultrasonic treatment for 10 minutes, a uniform precursor solution A was obtained.
[0121] (3) Hydrothermal reaction: The precursor solution A prepared in step 2 and the pretreated nickel foam substrate were placed in a hydrothermal reactor, ensuring that the ratio of the solution volume to the nickel foam electrode area was maintained at 8 mL / cm 2 The reactor was placed at 120°C for 6 hours.
[0122] (4) Post-treatment: After the hydrothermal reaction is completed, the nickel foam electrode is taken out and rinsed three times with deionized water to remove the surface residue, and then dried in a vacuum drying oven at 80°C for 12 hours. After cooling to room temperature, the final LDH electrode material is obtained.
[0123] Comparative Example 2
[0124] Pretreatment of nickel foam: A rectangular nickel foam (1×1.5 cm) (thickness: 1.5 mm, 110 ppi) was ultrasonically treated in 2M HCl, deionized water, and anhydrous ethanol for 15 minutes to remove surface oxides and other contaminants. After removal, it was rinsed three times with deionized water, then dried in a vacuum drying oven at 80°C for 2 hours, and finally cooled to room temperature, which was recorded as NF.
[0125] Application Comparative Example 1
[0126] Using the electrode of Comparative Example 1, electrocatalytic reduction of nitrate to produce ammonia is performed in the following steps:
[0127] The electrode prepared in Comparative Example 1 was clamped in the working electrode clamp and placed together with the reference electrode saturated silver chloride electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 - -N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell with electrolyte.
[0128] Then, multiple linear sweep voltammetric curve tests are performed in the potential range of -1.2 to -1.8 V vs. Ag / AgCl until the curves of two adjacent tests are exactly the same.
[0129] The electrolyte was replaced and it tests were carried out at four potentials of -1.2, -1.4, -1.6 and -1.8 V respectively. The test time was 7200 s. Samples were taken every 1200 s and kept for later use. Each set of experiments was repeated at least three times.
[0130] In addition, using NaNO3 and NaNO2 as standard samples, high performance ion chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0131] like Figure 5 As shown in the figure, the best test effect is achieved when the LDH electrode of Comparative Example 1 is used at a voltage of -1.4 V at room temperature and pressure. The conversion rate of nitrate is 56%, the generation rate of nitrite is 0%, and the generation rate of ammonia is 49%.
[0132] Application Comparative Example 2
[0133] Using the electrode of Comparative Example 2, electrocatalytic reduction of nitrate to produce ammonia is performed in the following steps:
[0134] The electrode prepared in Comparative Example 2 was clamped in the working electrode clamp and placed together with the reference electrode saturated silver chloride electrode and the platinum counter electrode in a solution containing 50 mg / L NO3 - -N, 0.1mol / L SO4 2- In a single-chamber electrolytic cell with electrolyte.
[0135] Then, multiple linear sweep voltammetric curve tests are performed in the potential range of -1.2 to -1.8 V vs. Ag / AgCl until the curves of two adjacent tests are exactly the same.
[0136] The electrolyte was replaced and it tests were carried out at four potentials of -1.2, -1.4, -1.6 and -1.8 V respectively. The test time was 7200 s. Samples were taken every 1200 s and kept for later use. Each set of experiments was repeated at least three times.
[0137] In addition, using NaNO3 and NaNO2 as standard samples, high performance ion chromatography was used to determine the nitrate and nitrite contents in the electrolyte before and after electrolysis; using ammonium chloride as a standard sample, ultraviolet absorption spectroscopy was used to determine the ammonia content in the electrolyte before and after electrolysis.
[0138] like Figure 6 As shown in the figure, under normal temperature and pressure, the NF electrode of Comparative Example 2 has the best test effect at a voltage of -1.4 V. The conversion rate of nitrate, the generation rate of nitrite and the generation rate of ammonia are 22%, 0% and 20%, respectively.
[0139] The above results show that the POM intercalated layered structure material in the present invention exhibits significant performance advantages in the electrocatalytic nitrate reduction to produce ammonia reaction. Compared with electrodes containing only layered structure materials and comparative electrodes containing only nickel foam (NF), these composite materials exhibit higher catalytic activity and selectivity. The intercalation of POM not only enhances the stability and electron transfer ability between the layers of the layered structure material, but also provides additional active sites, thereby significantly improving the overall performance of the electrode. In the comparative experiment, the non-intercalated layered structure material electrode and the electrode using only nickel foam were significantly inferior in performance, further verifying the key role of POM intercalation in improving electrode performance.
[0140] When studying the electrocatalytic performance of POM intercalated layered structure material composites, the d-band center theory provides an important theoretical basis for understanding the activity of the catalyst. The d-band center refers to the average position of the d-orbital electron energy level in transition metal catalysts. Generally, the closer the d-band center is to the Fermi level, the higher the activity of the catalyst, because the position of the d-band center directly affects the interaction between the catalyst and the reactant (such as NO3 - ), thus affecting the electron transfer ability and adsorption energy.
[0141] In the POM intercalation layered structure material of the present invention, the intercalation of POM significantly regulates the d-band center position of the material. - The intercalated CuNi LDH showed the best electrocatalytic performance, which can be attributed to the VO3- Intercalation causes the d-band centers of Cu and Ni to approach the Fermi level, thus enhancing the NO3 - The adsorption and activation capacity of VO3 - It has a high electron accepting capacity and can react with NO3 - The π* orbitals of NO3 undergo effective orbital overlap, promoting - This electronic structure optimization makes VO3 - Intercalated CuNi LDH in NO3 - It exhibits the highest catalytic activity in the reduction reaction. MoO4 2- The intercalated CuNi-LDH performs slightly worse than VO3 - The intercalated composite material still maintains high catalytic activity. MoO4 2- Due to its larger molecular structure, although it stabilizes the LDH interlayer structure, it also makes the d-band center slightly away from the Fermi level. 2- The multi-electron transfer ability in NO3 - The reduction process of NO3 - In contrast, WO4 2- The intercalated CuNi LDH exhibited slightly lower catalytic performance than MoO4 2- The main reason is WO4 2- The d-band center of NO3 is further away from the Fermi level, resulting in - The adsorption energy of WO4 is reduced, and the electron transfer efficiency is inhibited to a certain extent. 2- The larger ionic radius of the LDH may result in its poor intercalation performance compared to MoO4 2- and VO3 - Tight, thus reducing the reactivity. NbO3 - The intercalated CuNi LDH showed relatively low catalytic activity in the experiments of the present invention. This may be due to the fact that NbO3 - The d-band center of Cu and Ni is far away from the Fermi level, which weakens the effect of NO3 - Although NbO3 - It has strong stability, but due to its effect on electron transfer and NO3 - The promotion effect on the reduction reaction is limited, resulting in its overall performance in this reaction being inferior to that of other POM intercalation materials.
[0142] In summary, the intercalation of POM regulates the d-band center position of the layered structure material and improves the NO3 -The adsorption capacity and electron transfer efficiency of POM were improved, and the electrocatalytic performance was significantly improved by optimizing the electronic structure of the electrode surface. The POM intercalated layered structure material is significantly better than the unintercalated comparative electrode in terms of stability and catalytic activity, demonstrating its wide application potential in environmentally friendly ammonia production processes and providing new ideas for understanding and designing efficient electrocatalytic materials.
Claims
1. An electrocatalytic material for reducing nitrate to produce ammonia based on a layered structure material, characterized in that: The electrocatalytic material is a composite material based on a layered structure material; the composite material is formed by a composite of a layered structure material and an intercalation material polyoxometalates POMs, and the layered structure material and POMs are compositely constructed into a composite structure with an intercalation structure, that is, POMs, as a functional intercalation substance, are inserted between layers of the layered structure material to form an intercalation structure.
2. The electrocatalytic material for reducing nitrate to produce ammonia based on a layered structure material according to claim 1, characterized in that: The layered structure material is layered double hydroxide (LDH) or other materials with a layered structure.
3. The electrocatalytic material for reducing nitrate to produce ammonia based on a layered structure material according to claim 2, characterized in that: The layered structural material is a layered double hydroxide CuNi-LDH composed of copper and nickel elements, and its components are Cu(OH)2 and Ni(OH)2.
4. The electrocatalytic material for reducing nitrate to produce ammonia based on a layered structure material according to claim 1, characterized in that: The polyoxometalate is selected from VO3 - 、MoO2 - 、NbO3 - WO4 2- One or more of .
5. The electrocatalytic material for reducing nitrate to produce ammonia based on a layered structure material according to claim 4 or 5, characterized in that: The molar percentage of the copper element and the nickel element of the CuNi-LDH is 40-60%:40-60%, and the proportion of the POM intercalation material is 2-3% of the total molar amount of the copper element and the nickel element of the CuNi-LDH.
6. An electrode for producing ammonia by electrocatalytic reduction of nitrate based on a layered structure material, the electrode comprising a base nickel foam and an electrocatalytic material formed on the surface of the nickel foam, characterized in that: The electrocatalytic material is an electrocatalytic material for reducing nitrate to produce ammonia based on a layered structure material as described in any one of claims 1 to 6.
7. A method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia based on a layered structure material as claimed in claim 6, characterized in that: The steps include: 1) Remove impurities from the surface of nickel foam, wash and dry it for later use; 2) adding a non-precious metal salt forming a layered structure material according to a molar percentage, dissolving it in deionized water, and then adding a POM precursor forming a POM intercalation material; adjusting the pH value of the solution to an appropriate range, and ultrasonically treating to ensure uniform mixing of the solution, to obtain a precursor solution A; 3) placing the precursor solution A prepared in step 2 and the pretreated nickel foam substrate into a hydrothermal reaction kettle, and placing the reactor at 100-130° C. for a hydrothermal reaction for 6-12 hours; 4) After the hydrothermal reaction is completed, the nickel foam electrode is taken out, cleaned and dried to obtain the ammonia-producing electrode.
8. The method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia based on layered structural materials according to claim 7, characterized in that: In step 2), adding non-precious metal salts to form layered structure materials by molar percentage refers to: adding Cu(NO3)2·3H2O and Ni(NO3)2·6H2O in a molar ratio of 40-60%:40-60%; adding POM precursors to form POM intercalation materials refers to: adding Na2WO4·2H2O, NaVO3, NaMoO2·2H2O or NaNbO3, and the amount of POM precursor added is such that the total molar ratio of the intercalation material to the non-precious metal salts to form the layered structure material is 2-3%.
9. The method for preparing an electrode for electrocatalytic reduction of nitrate to produce ammonia based on layered structural materials according to claim 7, characterized in that: During the hydrothermal reaction in step 3), the ratio of the volume of the solution in the hydrothermal reaction kettle to the surface area of the nickel foam electrode is 5-20 mL / cm 2 ; In step 2), the pH value of the solution is adjusted to be in the range of 8 to 10.
10. A method for producing ammonia by electrocatalytic reduction of nitrates, characterized in that: The ammonia-producing electrode according to claim 6 is used as a self-supporting integrated electrode in an electrochemical system to electrocatalytically reduce nitrate to generate ammonia.